Polymorphism of electrospun polyvinylidene difluoride/carbon nanotube (CNT) nanocomposites : synergistic effects of CNT surface chemistry, extensional force and supercritical carbon dioxide treatment - Yee, Wu Aik (2013)
In this work, the effects of single-walled carbon nanotubes (SWCNT) surface chemistry on the polymorphism behaviors of electrospun poly(vinylidene difluoride) (PVDF) nanofibers collected under high extensional force and subsequently treated with supercritical carbon dioxide (SCCO2) are investigated via X-ray diffraction, infrared and Raman spectroscopy. It is found that the SWCNTs with hydroxyl groups (h-SWCNTs) interact with PVDF chains more intensively than the ones with ester groups, and the interaction in couple with the high extensional force promotes the formation of β-form extended-chain crystallites (ECCs). With the SCCO2 treatment, the growth of the β-form ECCs is further promoted in the PVDF/h-SWCNT nanofibers owing to the synergistic effect of the strong confinement effect of h-SWCNT for stabilizing the nuclei of the β-form ECCs and the high pressure applied.